Implementasi Model Project Based Learning untuk Meningkatkann Keterampilan Dasar Mengajar yang Dimiliki oleh Mahasiswa Calon Guru - Hikmawati Hikmawati; I Wayan Suastra (Kappa Journal, 2022)
Basic teaching skills are the competencies of prospective teacher students that must be trained before they teach directly in the real class. The purpose of this study is to improve the basic teaching skills possessed by prospective teacher students through the implementation of the Project Based Learning (PjBL) model. The research subjects included all prospective physics teacher students who took part in the following lectures: Micro Teaching in Class VI-E, Physics Education Study Program, University of Mataram, Academic Year 2021/2022, as many as 15 students. The project assigned was in the form of making the 1st teaching simulation video and 2nd teaching simulation video. The basic teaching skills assessment instrument is an observation sheet on a teaching simulation video which includes eight components, namely: opening and closing lessons skills, classroom management skills, skills to provide reinforcement, skills to guide small group discussions, basic questioning skills, advanced questioning skills, skills to explain lessons, variety skills. The assessment score uses a scale of 5 which is then expressed in the form of a percentage. The increase in score was calculated using the N-gain test. The results showed that the initial score was 65.0, while the final score was 83.7, so the N-gain value was 53.9. Thus, the basic teaching skills possessed by prospective physics teacher students through the implementation of the PjBL model increased with the improvement criteria being in the medium category.